Comparative analysis for performance measurements of software testing between mobile applications and web applications - Hassan Muhamad, Zainab (2015)
Software testing has an important role in software engineering, and is fundamental to Software Quality Assurance (SQA). Besides the popularity of web applications, mobile applications have gained paralleled advancement despite increasing complexity. On one hand, this issue reflects the rising concerns for ensuring performance both of web and mobile applications. On the other hand, a comparative analysis of software testing issues between web and mobile applications has not been completed. Thus, this study aims to employ an effective testing approach that is able to adapt both of web and mobile application testing to detect possible failures. To achieve this, UML activity diagrams were developed from four case studies for web and mobile applications to describe the behaviour of those applications. Test cases were then generated by using the MBT technique from the developed UML activity diagrams. Performance measurements Hits per Second, Throughput and Memory Utilization for each case study were evaluated by execution of test cases that were generated by using HP LoadRunner 12.02 tool. Finally, the MSE of performance measurements was compared and analysed among the four case studies. The experimental results showed that the disparity between the mobile applications and web applications was obvious. Based on the comparison analysis for software testing of mobile applications versus web applications that was the web applications were lesser than mobile applications for software testing of four case studies in terms each of the Hits per Second, Throughput and Memory Utilization. Consequently, mobile applications need more attention in the testing process.